OPTIMALISASI TRANSPOR Zn(II) DENGAN ZAT PEMBAWA DITIZON MELALUI TEKNIK MEMBRAN CAIR FASA RUAH - Tetra, Olly Norita; K, Zaharasmi; -, Refinel; Kurniawaty, Eka (Universitas Andalas, 2010)
ABSTRACT Zn(II) transport from the source phase into the source phase had been researched by using dithizone as carrier through bulk liquid membrane. Ion transport are started by adding 6 mL source phase that consist of Zn(II), 12 mL receiver phase that consist of Na2EDTA and 20 mL membrane phase that consist of dithizone as carrier. The experiment operation technique was assisted by magnetic stirrer mixing at 340 rpm speed within 15 minutes equilibrium time. The measurement was done to both of source phase and receiver phase by using Atomic Absorption Spectrophotometer (213.9 nm) until Zn(II) was transported to receiver phase and residue in source phase was gathered. The research result that optimum conditions to transport 3.06 x 10-4 M Zn(II) was at pH 8.5 of source phase, 1.75 x 10-5 M dithizone concentrate at membrane phase, 0.06 M EDTA concentrate at pH 6 in receiver phase and 3 hours transport time with Zn(II) percentage which was transported to receiver phase 93% and residue in source phase do not detect. Keywords: transport Zn(II), bulk liquid membrane, dithizone